A Diketopiperazine, Cyclo-(L-Pro-L-Ile), Derived From Bacillus thuringiensis JCK-1233 Controls Pine Wilt Disease by Elicitation of Moderate Hypersensitive Reaction - Park, Ae Ran; Jeong, Se-In; Jeon, Hee Won; Kim, Jueun; Kim, Namgyu; Ha, Manh Tuan; Mannaa, Mohamed; Kim, Junheon; Lee, Chul Won; Min, Byung Sun; Seo, Young-Su; Kim, Jin-Cheol (Frontiers in Plant Science, 2020)
Pine wilt disease (PWD) caused by the pine wood nematode (PWN) Bursaphelenchus xylophilus is one of the devastating diseases affecting pine forests worldwide. Although effective control measurements are still missing, induction of resistance could represent a possible eco-friendly alternative. In this study, induced resistance-based in vitro and in vivo screening tests were carried out for selection of bacteria with the ability to suppress PWD. Out of 504 isolated bacteria, Bacillus thuringiensis JCK-1233 was selected for its ability to boost pathogenesis-related 1 (PR1) gene expression, a marker of systemic acquired resistance. Moreover, treatment of pine seedlings with B. thuringiensis JCK-1233 resulted in increased expression of other defense-related genes, and significantly inhibited PWD development under greenhouse conditions. However, B. thuringiensis JCK-1233 showed no direct nematicidal activity against B. xylophilus. To identify the effective compound responsible for the induction of resistance in B. thuringiensis JCK-1233, several diketopiperazines (DPKs) including cyclo-(D-Pro-L-Val), cyclo-(L-Pro-L-Ile), cyclo-(L-Pro-L-Phe), and cyclo-(L-Leu-L-Val) were isolated and tested. Foliar treatment of pine seedlings with Cyclo-(L-Pro-L-Ile) resulted in suppression of PWD severity and increased the expression of defense-related genes similarly to B. thuringiensis JCK-1233 treatment. Interestingly, treatment with B. thuringiensis JCK-1233 or cyclo-(L-Pro-L-Ile) showed moderately enhanced expression of PR-1, PR-2, PR-3, PR-4, PR-5, and PR-9 genes following inoculation with PWN compared to that in the untreated control, indicating that they mitigated the burst of hypersensitive reaction in susceptible pine seedlings. In contrast, they significantly increased the expression levels of PR-6 and PR-10 before PWN inoculation. In conclusion, foliar spraying with either B. thuringiensis JCK-1233 culture suspension or DPKs could induce resistance in pine seedlings, thereby alleviating the serious damage by PWD. Taken together, this study supports aerial spraying with eco-friendly biotic or abiotic agents as a valuable strategy that may mark an epoch for the control of PWD in pine forests.